The role of monetary policy in achieving financial stability of Iraqi banks for the period (2009 - 2017) - موسى حيدر طالب; مهدي صباح رحيم; عذافه حيدر حسين (Journal of Economics and Administrative Sciences, 2020)
The responsibility of the Central Bank through the implementation of its monetary policy to maintain the integrity and stability of the financial system and the economic system, because any shock, whether internal or external, may endanger the financial system and instability, so the research sheds light on the effectiveness of monetary policy in maintaining financial stability, The most important conclusion is that there is an increase in capital, which gives banks the possibility to face the risks to which they are exposed, as well as a rise in the total bad debts, which weakens its financial position, which constitutes a decline in the financial stability of these banks.